Brain Rot dan Krisis Literasi di Kalangan Pelajar Indonesia - Anisaturrizqi, Rita (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
The phenomenon of brain rot that is rampant among Indonesian students reflects the literacy crisis in the era of rapid and superficial digital consumption. This study analyzes the correlation between the intensity of exposure to instant digital content and the decline in critical literacy skills and reading interest among Indonesian students. Based on national and international data such as PISA 2022, as well as theoretical approaches such as Cognitive Load Theory, Uses and Gratification, and the concept of Digital Natives, this research explores how instant information consumption diminishes students' focus, working memory, and reflective capacity. In response, this study offers 21st-century literacy strategies through the strengthening of critically-based digital literacy, reflective pedagogical innovations such as slow reading and deep learning. This finding emphasizes that the literacy crisis in the digital era is not only a matter of low reading interest but also a direct result of the dissonance between the education ecosystem and students' digital culture.